Development of Problem-based Blended Learning (PB2L) model to increase pre-service primary teacher’s creative thinking skill - Wahyudi Wahyudi; Budi Waluya; Hardi Suyitno; Sutriyono Sutriyono; Indri Anugraheni (Intelektual Pustaka Media Utama, 2019)
Problem-based learning is generally done with face-to-face interaction. This learning process, however, has not provided a lot of time for learners to find limitless and timeless information and learning resources. It still depends on the teacher as a source of information. Students are very dependent on the presence of lecturers during face-to-face interaction. This research aims to develop a Problem-based Blended Learning (PB2L) model to support student to improve their creative thinking skills. The method used in this research was R and D with ASSURE development model. Product validation was done through an expert’s assessment by using the expert’s validation sheet. The practicality of the product is tested with limited trials with college lecturers and some students with questionnaires and interviews. Product effectiveness was seen by implementing limited development testing to a particular class with a one group pretest-posttest design and the result was analyzed by using a Paired-Samples T-Test. The result of this research is a Problem-based Blended Learning (PB2L) valid, practical and effectively improves students' creative thinking abilities. The effectiveness of the learning model was also proven on the basis of Paired-Samples T-Test of students’ pretest and posttest with sig. (2-tailed) 0.000. This learning gives students the opportunity to think systematically by beginning by criticizing the interesting contextual problems and ending with meaningful reflection with adequate learning resources both in face-to-face and online interaction.